Twenty Years of Kaniadakis Entropy: Current Trends and Future Perspectives - Dionissios T. Hristopulos; Sérgio Luiz E. F. da Silva; Antonio M. Scarfone (Entropy)
Napier’s number <semantics>e=2 [...]</semantics>